Strategic deployment of GIS-optimized solar charging stations for electric vehicles: A multi-criteria decision-making approach - Marziyeh Razeghi; Ali Roghani Araghi; Amir Naseri; Hossein Yousefi (Energy Conversion and Management: X)
Climate change and the rise in carbon dioxide levels due to gasoline vehicles are global challenges that require innovative and sustainable solutions; this study presents an innovative strategy to promote electric vehicles (EVs) adoption through the establishment of solar-powered charging stations. Utilizing ArcGIS10.8.2 software, a comprehensive analysis was conducted to identify optimal locations for these stations, considering technical, economic, environmental, and geological data. This research, unlike other past research, leverages public spaces such as gas stations, shopping centers, and parking lots for station construction, minimizing operational costs and fostering a sustainable infrastructure. This approach applies not only to the study area of this research, which is Khuzestan province, but can also be extended to other regions and serves as a model for reducing CO2 emissions in the transportation sector worldwide. This research evaluates the location for establishing electric vehicle charging stations using solar energy innovatively, from both technical and operational perspectives. By using the systematic and new method presented in this research, it is possible to identify the highest potential for the construction of electric car charging stations that simultaneously use solar energy all over the world, and the results of applying this new method in the studied area showed that 90 % of the cities within this province have the potential to establish charging stations for electric vehicles utilizing sunlight. Specifically, Mahshahr County in this province can supply 90.55 % of the required energy for charging stations through solar energy. Operationally, 70 % of the cities in the region possess such potential. The study demonstrated that this area has the capacity to convert 11 % of vehicles to electric cars by 2040 and can reduce CO2 emissions by more than 30 tons.